Information Dynamics of Cotton Farmers in Akola District of Maharashtra - V. K., Sajesh; Padaria, R. N. (Indian Journal of Extension Education, 2017)
Access to information is of crucial importance in the present agricultural scenario. The present study was conducted at  Akola district of Maharashtra to analyse the information need and information search behavior of cotton farmers.  Department of Agriculture, followed by friends and neighbours, input dealers and other progressive farmers were the  major sources of information contacted by most of the farmers. Contact frequency of farmers was found to be varying  widely with farmers with lower number of information sources found to be relying more on input dealers, radio, television  and newspapers. Major information needs of farmers were found to be related to pest management, seeds of new varieties,  seed treatment, water management and soil fertility.
Keywords: Cotton; Information Need; Information Search Behaviour